Optimizing IT Project Management in Ukraine's Aviation Sector: Challenges, Opportunities, and Strategic Insights - Zhyvko Zinaida; Zsivkó Z.; Живко З.; Zhyvko Mykhailo; Zsivkó M.; Живко М.; Shehynska Anastasiia; Sehinszka A.; Шегинська А. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The Ukrainian aviation industry is undergoing digital transformation; however, the pace remains behind global and European standards due to several challenges. These include limited funding, a lack of skilled IT professionals, and a slow rate of modern technology adoption. The research, titled "Optimizing IT Project Management in Ukraine’s Aviation Sector: Challenges, Opportunities, and Strategic Insights," addresses the urgent need for improvements in IT project management to enhance efficiency, competitiveness, and technological advancement within the aviation sector in Ukraine. This article analyzes the sector's current challenges, including insufficient government and private sector investment, internet infrastructure issues, and a shortage of IT specialists. It also identifies opportunities in areas like automation, digitization, and the potential for public-private collaborations. The study's primary objective is to develop and evaluate an optimal IT project management framework tailored to Ukraine’s aviation industry. This framework aims to optimize resource usage, integrate modern technologies like AI, automation, and cybersecurity, and improve global competitiveness. Furthermore, the research offers a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis of Ukraine’s aviation IT landscape, benchmarking it against European standards. A substantial gap exists between Ukraine and Europe regarding IT investment and automation, with European countries leading in adopting AI-driven systems, enhanced cybersecurity, and automated business and customer service processes. To bridge this divide, the study proposes an optimized IT project management model focused on strategic priorities such as investment in skill development, strengthening public-private partnerships, enhancing cybersecurity, implementing agile work methods, and supporting innovation through government initiatives. In conclusion, the study underscores that enhancing IT project management in Ukraine’s aviation industry is crucial for maintaining global competitiveness and improving operational efficiency. The proposed model offers actionable insights to address current challenges while capitalizing on new opportunities, thereby ensuring resilience in the face of ongoing global digitization and technological advancements.

A gazdaság minden ágazata, így a légi közlekedés is jelenleg a digitális átalakulás szakaszában van, de ennek a folyamatnak az üteme messze elmarad a világ és az európai színvonalától. A korlátozott finanszírozást tekintik a gazdaság fejlődését gátló fő problémának, emellett sürgető a személyi kérdés - a magasan kvalifikált szakemberek hiánya, különösen most a háború alatt az informatikusok külföldre kiáramlása és a legújabb technológiák lassú és nem megfelelő bevezetése. A cikk a légiközlekedési ágazat előtt álló fő kihívásokat és lehetőségeket vizsgálja. A cikk célja, hogy feltárja az informatikai projektek menedzselésének javításának módjait az ország légiközlekedési ágazatának általános hatékonyságának és versenyképességének növelése érdekében. A szerzők az ukrajnai légiközlekedési IT szektor erősségeit és gyengeségeit vizsgálják, összehasonlítva az európai mutatókkal valamint a kiberbiztonság biztosításában. Ennek a szakadéknak a csökkentése érdekében az IT projektmenedzsment továbbfejlesztett modelljét javasolják, amely magában foglalja az állam és a magánszektor aktív részvételét, az innovatív projektek támogatását és a nemzetközi szintű együttműködés kiterjesztését. A cikk egyik feladata egy olyan modell megalkotása, amely hozzájárul a modern technológiák integrálásához az informatikai projektmenedzsment folyamatokba, növeli az erőforrás-felhasználás hatékonyságát, valamint növeli az ukrán légiközlekedési ágazat általános versenyképességét a világpiacon. A modell alkalmazásának köszönhetően a tervek között szerepel a személyi kérdések javítása (magasan képzett informatikai dolgozók képzése), a finanszírozás javításának módjai (belső és külső beruházások), a kiberbiztonság szintjének javítása (a fenyegetések lokalizálása és megszüntetése, információszivárgási csatornák blokkolása). A szerzők által megfogalmazott fő következtetés azt bizonyítja, hogy az ukrán légiközlekedési szektor versenyképességének megőrzése érdekében az informatikai projektmenedzsment jelentős optimalizálására van szükség, amely nemcsak a meglévő kihívások leküzdését, a veszélyek lokalizálását és azok kiküszöbölését teszi lehetővé, hanem lehetővé teszi a légiközlekedési ágazat fejlesztésének új lehetőségeinek kihasználását, figyelembe véve a technológiai haladás és az intelligens gazdaság fejlődésének globális trendjeit.

Резюме. Всі галузі економіки, в тому числі і авіаційна, в умовах сьогодення перебувають на етапі цифрової трансформації, однак темпи цього процесу значно відстають як від світових, так і від європейських стандартів. Основними проблемами, які гальмують розвиток економіки, вважається перш за все обмежене фінансування, крім того гостро постає кадрове питання – недостатність висококваліфікованих спеціалістів, особливо зараз в період війни через відтік ІТ-спеціалістів за кордон та повільне і неналежне впровадження новітніх технологій. В статті розглядаються основні виклики та можливості, які стоять перед авіаційним сектором. Сформована мета статті – можливості для вивчення шляхів вдосконалення управління ІТ-проєктами для підвищення загальної ефективності та конкурентоспроможності авіаційної індустрії країни. Автори проводять аналіз сильних та слабких сторін авіаційного ІТ-сектору в Україні, порівнюючи його з європейськими показниками.За проведеним аналізом – європейські країни випереджають Україну за рівнем автоматизації та впровадження штучного інтелекту в операційні процеси, а також у забезпеченні кібербезпеки. Для скорочення цього розриву пропонується вдосконалена модель управління ІТ-проєктами, яка передбачає активну участь держави і приватного сектору, підтримку інноваційних проєктів та розширення співпраці на міжнародному рівні. Одним із завданням статті є створення моделі, яка сприятиме інтеграції сучасних технологій у процеси управління ІТ-проєктами, підвищенню ефективності використання ресурсів, а також підвищення загальної конкурентоспроможності української авіаційної індустрії на світовому ринку. Завдяки застосування даної моделі планується покращити кадрове питання (підготовка висококваліфікованих працівників ІТ-сфери), знайти шляхи покращення фінансування (внутрішні та зовнішні інвестиції), покращити рівень кібербезпеки (локалізувати та усунути загрози, перекрити канали витоку інформації). Основний висновок, який декларується авторами, засвідчує що для підтримки конкурентоспроможності українського авіаційного сектору необхідна суттєва оптимізація управління ІТ-проєктами, що дозволить не лише подолати існуючі виклики, локалізувати загрози та усунути небезпеки, а й використати нові можливості для розвитку авіаційної сфери, враховуючи глобальні тенденції розвитку технологічного прогресу та смарт-економіки.
Оптимізація управління ІТ-проєктами в авіаційному секторі України: виклики, можливості та стратегічні висновки
IT projektmenedzsment optimalizálása Ukrajna légiközlekedési szektorában: kihívások, lehetőségek és stratégiai következtetések
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/7
Keywords: aviation industry; IT project management; flexible methodologies; public-private partnership; innovation strategy; SWOT analysis; artificial intelligence; digital transformation; integration into the economy; IT project management model